How case representations of medical students change during case processing – Results of a qualitative study - Braun, Leah Theresa (GMS J Med Educ, 2018)
Objective: Representations are mental summaries of a clinical case and help in understanding a clinical problem. However, it is still largely unknown which clinical information medical students include in their case representations. In this study, therefore, the structure and quality of students’ case representations were examined to better understand the diagnostic process and its relationship to diagnostic accuracy. What information do medical students include in their representations and is there an association between this information and the diagnostic accuracy? Method: 43 medical students in the fourth and fifth clinical year worked on four clinical cases. During the diagnostic process, they were asked three times per case to write a case representation. 516 representations were qualitatively evaluated using a content-based coding scheme. An analysis was made of the nature and composition of the clinical information. In addition, the association between the general representation structure and the correct case solution was examined. Results: At the beginning, students include most of the clinical information in their representation (66%), but as the case progresses, they begin to select the information offered (2nd representation 42%, 3rd representation 38%). The length of the representation (number of words) does not correlate with the correct case solution (r=-0.08-0.31). The representations do not depend on the case difficulty but have a significant individual component: the representations written by a student are formally very similar in all four cases (r=0.60-0.86). Conclusion: Medical students can select the relevant clinical information and include it in their case representations. Lack of representation does not seem to be a reason for misdiagnosis; Students’ deficits in diagnosis are more likely due to knowledge gaps.